2020
DOI: 10.3390/ani10020250
|View full text |Cite
|
Sign up to set email alerts
|

The Association of the Copy Number Variation of the MLLT10 Gene with Growth Traits of Chinese Cattle

Abstract: Copy number variation is a part of genomic structural variation and has caused widespread concern. According to the results of high-throughput screening of the MLLT10 gene, we found that the copy number variation region of the MLLT10 gene was correlated with bovine growth traits. We aimed to detect the MLLT10 gene copy number variation and provide materials for the Chinese yellow cattle breed. In this study, the SPSS software was used to analyze the correlation among the copy number type of six different cattl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…These genes included GPX5 , GPX6 (reproductive performance) [ 33 ], SLC2A5 (feed efficiency) [ 34 , 35 , 36 ], IGLL1 [ 37 ] and BOLA-DQA2 , BOLA-DQB (immunity) [ 8 , 38 , 39 , 40 ]. It is worth noting that the MLLT10 gene, which is associated with fat deposition [ 41 ], was detected in both the two methods, indicating that the mentioned genes were strongly selected in Dabieshan cattle. The positive selection signals around the region of MLLT10 (BTA13: 22.74–22.95 Mb) were further recapitulated by significantly lower values of nucleotide diversity and Tajima’s D in Dabieshan cattle ( Figure 3 b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These genes included GPX5 , GPX6 (reproductive performance) [ 33 ], SLC2A5 (feed efficiency) [ 34 , 35 , 36 ], IGLL1 [ 37 ] and BOLA-DQA2 , BOLA-DQB (immunity) [ 8 , 38 , 39 , 40 ]. It is worth noting that the MLLT10 gene, which is associated with fat deposition [ 41 ], was detected in both the two methods, indicating that the mentioned genes were strongly selected in Dabieshan cattle. The positive selection signals around the region of MLLT10 (BTA13: 22.74–22.95 Mb) were further recapitulated by significantly lower values of nucleotide diversity and Tajima’s D in Dabieshan cattle ( Figure 3 b).…”
Section: Resultsmentioning
confidence: 99%
“…The increased SLC2A5 expression was associated with an enhanced relative growth rate and Kleiber index in Nelore steers [ 36 ]. The copy number variation of the MLLT10 gene sensibly influenced the growth traits of two Chinese native cattle breeds [ 41 ]. Similarly, the MLLT10 gene had a feed conversion ratio (FCR) regarding male Duroc pigs [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…, where Y ijk is observed for growth traits, μ is the population mean for growth traits, A i is the effect due to the age of ith, G j is the effect due to CNV type of each point and e ijk is the random residual (Z. Xu et al, 2020;Yang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In the data processing, according to the different factors affecting the body size traits, considering age and genetic effects, the fixed model was used for analysis, and simplified according to the actual situation. To analyze the effect on phenotypic traits, we used the following model: Y ijk = μ + A i + G j + e ijk , where Y ijk is observed for growth traits, μ is the population mean for growth traits, A i is the effect due to the age of ith , G j is the effect due to CNV type of each point and e ijk is the random residual (Z. Xu et al., 2020 ; Yang et al., 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…For example,Hou et al (2011) found that the loss, median and gain types of SCP2, ULBP and WC1.1 genes were related to lipid transport metabolism in cattle;Stothard et al (2011) found that the change in copy number of the PLA2G2D gene was related to milk yield and meat quality Bickhart et al (2012). found that the involvement of the repetitive myosin heavy chain 1 gene in skeletal muscle development was related to bovine growth traits Yang et al (2020),. through the association analysis of MLLT10 gene CNVs and the growth traits of Chinese native…”
mentioning
confidence: 99%